Barriers to optimal control of Type 2 diabetes in Malaysian Malay patients - Mohd Ali, Salmiah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
There are a growing number of people diagnosed with diabetes. But, with the growing number of people diagnosed with diabetes, Malaysia is not spared of this phenomenon, as prevalence stands at 14.9% of adult population. Adequate blood glucose control is vital in diabetes management to prevent complications. Even so there is a lack of diabetic control among people with diabetes in Malaysia and we need to understand why this is. This study set out to explore the perspectives and experiences of Malay patients in managing Type 2 diabetes as a chronic illness and provide recommendations that aim to enhance adherence to treatment and help patients to improve their self-management skills. In-depth interviews were carried out on a purposeful sample of patients and their health care professional (HCPs). Interviews were recorded, transcribed and audiotapes were analysed using NVivo software to identify emerging themes and code according to categories. Interviews were conducted in an Endocrinology clinic in Malaysia with 18 Malay patients (15-75 years, 9 males and 9 females) and 13 HCPs. Results indicated that themes that emerged from interviews with the patients included problems with integrating the treatment regimen and difficulty developing coping skills to achieve the desired blood glucose level. Most patients lacked understanding of diabetes and management of diabetes, nature of diabetes, awareness of having diabetes, diabetic education, knowledge of diabetes, duration of illness, patients’ understanding of diabetes, physical effects of treatment, severity of symptoms and disease. Patients believed that they needed to integrate many treatment requirements such as diet, medications, blood glucose monitoring and exercise into their daily routine. However, barriers to achieving good control of diabetes were found to be the constraints in their ability to control diabetes. Education and knowledge related to diabetes that influenced understanding of the disease were also reasons for non-adherence to treatment regimen. Their beliefs and ability to minimise these barriers shaped their attitudes towards disease management. Patients were willing to discuss their problems about self-managing diabetes if some of these barriers were addressed during consultations. It can be concluded that more positive approaches are needed in self-management of diabetes and health care professionals involved in the management of diabetes need to understand their patients’ beliefs about their diabetes and constraints faced by their patients to promote more awareness and to foster greater control of diabetes and improve health outcomes.